Dynamics Model of Gear Hobbing Vibration based on Time-varying Cutting Force - Xia Yu; Wang Shilong; Wang Shuangbu (Jixie chuandong)
The time-varying cutting force in the process of gear hobbing will cause chatter and affect the quality and the precision of workpiece. To analyze the vibration characteristics of hob and workpiece system,according to the theory of metal cutting,a calculation method of the time-varying cutting force is proposed,by considering single tooth cutter and double-tooth cutter. At the same time,a dynamics model of gear hobbing vibration with four degrees-of-freedom is established,the effects of different rotational speed on the vibration characteristics are obtained. Also,a vibration experiment of gear hobbing is carried out,and the dynamics model is proved to be correct based on contrastively analyzing the experimental data and the results of theoretical calculation. The results of study show that the new calculation method can calculate the vibration characteristics of the hob and workpiece accurately,which can provide a basis for studying the mechanism of cutting chatter and monitoring the conditions of machining system.